Finding the Generalized Forces of a Series-Parallel Manipulator. (3rd January 2013) - Garcia-Murillo, Mario; Gallardo-Alvarado, Jaime; Castillo-Castaneda, Eduardo
In this work the kinematic and dynamic analyses of a robot manipulator whose topology consists of parallel kinematic structures with linear actuators are approached by means of the theory of screws and the principle of virtual work. The input/output equations of velocity and acceleration are obtained by applying screw theory. Then the generalized forces of the manipulator are determined combining screw theory and the principle of virtual work. Finally, a case study, whose numerical results are compared with simulations generated with the aid of specialized software, is included.